IKROM OTAMUROD DOSTONLARIDA FALSAFIY MUSHOHADALAR TAHLILI - Jumayeva, S. (SCIENCE and SOCIETY, 2022)
The success of reforms in society largely depends on the spiritual and social level of members of the society. In the formation of any human spirituality, fiction has a wide range of possibilities. In this sense, there is a need for systematic study of Ikram Atamurad work in poeme. The article determines the place of Ikram Atamurad in the Uzbek literature.